Advanced spatially hybrid fluid‐kinetic modelling of plasma‐edge neutrals and application to ITER case using SOLPS‐ITER. Issue 5 (2nd February 2022) - Van Uytven, W.; Dekeyser, W.; Blommaert, M.; Horsten, N.; Marandet, Y.; Baelmans, M.
Abstract: A spatially hybrid fluid‐kinetic approach for the efficient simulation of plasma‐edge neutrals is extended with a kinetic‐fluid condensation process and an automated approach to select a fluid or kinetic treatment at each point along the divertor targets. With the proposed hybrid fluid‐kinetic methods, the dominant charge–exchange reaction can be largely removed from the kinetic neutral simulation. The hybrid methods achieve quantitative agreement with the standard kinetic approach, with relative errors on the peak target plasma density and peak target ion flux density of 5–30%, while the Central Processing Unit (CPU) time for the kinetic neutral solver is reduced by a factor 3–6.